Kajian Kesesuaian Pembangunan Ruko Terhadap Kebutuhan Pasar di Kota Mataram - Khatimah, Husnul (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
Activity increase in Mataram causes the increase of land demand for settlement and trades facilities. The demand doesn’t match by sufficient land availability, thus shop-house (ruko) is seen as solution to fulfill the needs of housing and trades facilities. But today, the existence of shop-house has become problem, people consider the over-scattered and idle shop-house doesn’t bring maximal services delivery. Those conditions as the main consideration of the research with aim measuring whether the shop-house development really meet the market needs or not. Results of analysis shows that the effectiveness of each shop-house, is just in effective level (not reached maximum/very effective), but the spatial policy implementation discrepancies are still found in the some distric. This condition is caused by the existence of shop-house located outside the trade area as well as the number of shop-houses already exceeds the market needs, resulting in a massive untapped shop. An excess amount of shop-house is caused by lack of government control in granting permission to construct the shop-house and the speculative motive of the owners of capital. Handling the shop-houses that have been built and exceed the needs can be done by applying spatial sanctions, ranging from a written warning, suspension service shop, site closure, revocation of permits, demolition, restoration of function space and administrative fines.